Neonatal intensive care unit (nicu): The importance in survival of newborns - Batista, Gisele de Jesus (2021)
Introduction: The infant mortality rate has dropped significantly in recent decades in Brazil and worldwide, and represents an important indicator of the socioeconomic development of countries. It stands out that it contributes to increase the infant mortality rate, the high number of neonatal deaths. In this scenario, the Intensive Care Units (NICU) are configured in an appropriate environment for the treatment of critically ill newborns (NB), enabling the maintenance of life and the recovery of children's health. Objective: To carry out a systematic evaluation of the literature, evidencing the importance of the Intensive Care Unit in the protection and support of newborns. Methodology: bibliographic research seeks to explain and discuss a theme based on theoretical references published in books, magazines, periodicals and others. They also seek to know and analyze scientific content on certain topics. The data used in this research are characterized as secondary, that is, based on data already treated, taken from books and works to show the concept, treatment and its particularities. Results: A prematurity, for example, in addition to taking the NB to hospitalization in the NICU still exposes him to several painful procedures necessary to maintain his life. Therefore, it is important that health professionals understand the pathophysiology, the clinical manifestations of the neonate, the type and characteristics of pain, aiming at qualified clinical evaluation and appropriate therapeutic conduct and the importance of the performance of the intensive care unit in neonates. Conclusion: Child health care is still under construction, together with health care in general, in a movement of paradigmatic change from the model centered on pathology and the child, to a model of building networks, in favor of the inclusion of the family. and comprehensive care.